Coordinated operation of hydrogen refuelling and fast charging combo station under normal and contingent conditions. Issue 3 (27th October 2020) - Bao, Zhiyuan; You, Shi; Hu, Zechun; Wen, Yilin
Abstract: Fuel cell electric vehicles (FCEVs) are rapidly growing owing to the increased public awareness of energy and environmental issues. Infrastructure for hydrogen production, transportation, and allocation is essential for FCEV promotion. For consumers, availability of few hydrogen refuelling stations is the primary concern. Currently, public charging infrastructure for battery electric vehicles, for example, fast charging station, has a more widespread coverage compared to infrastructure for hydrogen refuelling. With an electrolyser, the existing power grid can be used as an alternative to hydrogen supply and transportation infrastructure, which is still being developed. The authors propose a new conceptual combo station acting as both a hydrogen refuelling station and a fast charging station. This station can satisfy the requirement of FCEVs and battery electric vehicles, and even operate under a blackout situation. To quantify the value of coordinated operation, an optimal operation formulation of a combo station is developed. It is found that such a combo station is capable of saving land rents, reducing power network reinforcement cost, and boosting energy self‐balance capability under blackout condition.